2000
DOI: 10.1088/0029-5515/40/11/311
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of cold pulses and heat pulses in ASDEX Upgrade

Abstract: Experiments on electron heat transport were performed in the tokamak ASDEX Upgrade, mainly in ohmically heated plasmas, applying either edge cooling by impurity injection or edge heat pulses with ECH. Repetitive pulses within one plasma discharge were made allowing Fourier transformation of the temperature perturbation. This yields a good signal to noise ratio up to high harmonics and allows a detailed investigation of the pulse propagation. For densities lower than 1:8 10 19 m ,3 , an increase of the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 22 publications
10
101
0
2
Order By: Relevance
“…Following the edge cooling, there was a rapid increase of the core electron temperature, on a time scale (∼5 ms) faster than the diffusive time. This effect is suggestive of a short-lived internal transport barrier (ITB), triggered by the sudden increase of the edge temperature gradient, which can be modeled with an abrupt drop in the core electron thermal conductivity [19,20,21,23,24,25,27], and which persists for the duration of the edge cooling (∼30 ms). A model for this transient increase in electron heat transport (a drop in thermal conductivity) is shown in Fig.3, with a 25% drop in χ e near r/a = 0.3 (solid to dash-dot lines).…”
Section: Methodsmentioning
confidence: 99%
“…Following the edge cooling, there was a rapid increase of the core electron temperature, on a time scale (∼5 ms) faster than the diffusive time. This effect is suggestive of a short-lived internal transport barrier (ITB), triggered by the sudden increase of the edge temperature gradient, which can be modeled with an abrupt drop in the core electron thermal conductivity [19,20,21,23,24,25,27], and which persists for the duration of the edge cooling (∼30 ms). A model for this transient increase in electron heat transport (a drop in thermal conductivity) is shown in Fig.3, with a 25% drop in χ e near r/a = 0.3 (solid to dash-dot lines).…”
Section: Methodsmentioning
confidence: 99%
“…and the Chandrasekhar function G GðvÞ ¼ UðvÞ À vU 0 ðvÞ 2v 2 (16) Relaxing the constraints Eqs. (4) and (5) practically means when running a gyrokinetic code that V k and T need not to be calculated at each time step and updated back into the collision scheme.…”
Section: A For Eulerian or Semi-lagrangian Schemesmentioning
confidence: 99%
“…These facts have been emphasised both theoretically: through the description of avalanching and spreading, [3][4][5][6][7][8][9] through the characterisation of nonlocal, nondiffusive behaviour 1,[10][11][12] and experimentally through some yet-to-be-understood experimental jigsaws: deep inconsistencies with a (fixed gradient) local and diffusive modeling have indeed been reported in perturbative (either hot or cold pulse) experiments, [13][14][15][16][17] off-axis heating experiments, 19,20 or whilst reporting Bohm-like scalings of the energy confinement time. 18 An accurate description of such dynamics requires the simultaneous and self-consistent treatment of the full gyrokinetic distribution function (full-f modeling), in full-torus (global) tokamak geometry and for a prescribed distribution of sources and sinks (flux-driven description).…”
Section: Introductionmentioning
confidence: 99%
“…In order to promote a better understanding of the electron heat transport, the electron heat transport analysis for both transient and steady state has been carried out diligently in many tokamaks 1-3 and helical systems. [4][5][6] One of the significant issues found in these studies is a "nonlocal transport phenomenon" observed in perturbation experiments on many tokamaks [7][8][9][10][11][12] and a few helical systems. 4 In particular, a rise of the core electron temperature T e invoked by the rapid cooling of the edge plasma has been observed in various tokamaks with both ohmically heated plasmas and plasmas with an auxiliary heating, such as electron cyclotron heating ͑ECH͒, at a sufficiently low density ͑e.g., Ref.…”
mentioning
confidence: 99%